Melatonin Alleviates the Impairment of Muscle Bioenergetics and Protein Quality Control Systems in Leptin-Deficiency-Induced Obesity - Yaiza Potes; Andrea Díaz-Luis; Juan C. Bermejo-Millo; Zulema Pérez-Martínez; Beatriz de Luxán-Delgado; Adrian Rubio-González; Iván Menéndez-Valle; José Gutiérrez-Rodríguez; Juan J. Solano; Beatriz Caballero; Ignacio Vega-Naredo; Ana Coto-Montes (MDPI AG, 2023)
Leptin is critically compromised in the major common forms of obesity. Skeletal muscle is the main effector tissue for energy modification that occurs as a result of the effect of endocrine axes, such as leptin signaling. Our study was carried out using skeletal muscle from a leptin-deficient animal model, in order to ascertain the importance of this hormone and to identify the major skeletal muscle mechanisms affected. We also examined the therapeutic role of melatonin against leptin-induced muscle wasting. Here, we report that leptin deficiency stimulates fatty acid β-oxidation, which results in mitochondrial uncoupling and the suppression of mitochondrial oxidative damage; however, it increases cytosolic oxidative damage. Thus, different nutrient-sensing pathways are disrupted, impairing proteostasis and promoting lipid anabolism, which induces myofiber degeneration and drives oxidative type I fiber conversion. Melatonin treatment plays a significant role in reducing cellular oxidative damage and regulating energy homeostasis and fuel utilization. Melatonin is able to improve both glucose and mitochondrial metabolism and partially restore proteostasis. Taken together, our study demonstrates melatonin to be a decisive mitochondrial function-fate regulator in skeletal muscle, with implications for resembling physiological energy requirements and targeting glycolytic type II fiber recovery.